Psychology and alchemy - Jung, C. G. (Carl Gustav), 1875-1961 (Jung, C. G. (Carl Gustav), 1875-1961. Collected works, 1968)
A study of the analogies between alchemy, Christian dogma, and psychological symbolism. Revised translation, with new bibliography and index.